Odontogenic Myxoma in the Maxilla: A Report of a Rare Case - Ali Shah, Syed Murad; Kundi, Jawad Ahmad; Khttak, Shahid Khan; Khttak, shahid Khan; Hameed, Tariq; Safdar, Mubah (Journal of Gandhara Medical and Dental Science, 2015)
SUMMARY The aim of this paper is to determine the unique and very interesting case of odontogenic myxoma, which involved the right maxilla and its sinus. Odontogenic myxomas are considered to be a benign odontogenic tumor with locally aggressive behavior and non-metastasizing neoplasm of the jaw bones. It represents an uncommon benign neoplasm comprising 3–6% of all odontogenic tumors. It is usually derived from the dental mesenchyme or periodontal ligament. Despite the benign nature of myxoma, there is a high rate of local recurrence after curettage alone and thus in certain cases adequate resection is the only option.